The Impact of TikTok Go Affiliate Marketing on Consumer Engagement and Travel Ticket Purchase Decisions - Nisrina Raniah; Osly Usman (Journal of Strategic Marketing and Innovation, 2026)
In the era of digital technology, customers' information-seeking and purchasing behaviors have undergone changes, especially in the tourism sector. TikTok Go is featured as an affiliate marketing platform, enabling creators to promote tourism products and services via interactive short video content. The purpose of this study is to examine the impact of TikTok Go affiliate marketing on the engagement with the brand and the decision to buy a tourism ticket. In this study, the mediators between the two variables, including consumer engagement, are also examined. A quantitative approach was applied, with a survey of users of TikTok who had come into contact with TikTok Go content promoting tourist destinations. The data analysis technique used was the Partial Least-Squares (PLS) Structural Equation Modeling (SEM) using SmartPLS 4.0 software. The findings indicate that there is a positive and significant relationship between affiliate marketing activities and the engagement of consumers and their willingness to purchase a tourist ticket. Additionally, consumer engagement also affects the customer's buying decisions. This was also found to be a mediator between affiliate marketing and purchasing decisions. These results show that the use of affiliate marketing on social networks is not only capable of engaging consumers but also helps to convert them into consumers who make purchases in the tourism sector. Theoretically, this study contributes to the development of digital marketing literature, while practically, it offers insights for players in the tourism industry on leveraging TikTok Go.